Characterization by Potentiometric Procedures of the Stability Constants of the Binary and Ternary Complexes of Cu(II) and Duloxetine Drug with Amino Acids - Amal M. Al-Mohaimeed; Asma A. Alothman (Journal of Chemistry)
Potentiometric titration method has been used to define stoichiometries and stability constants of ternary complexes of Cu(II) with duloxetine (D) and some selected amino acids (L). The protonation constants of the ligands and the stability constants of the binary and ternary complexes of Cu(II) with the ligands were calculated from the potentiometric data using the HYPERQUAD program. The formation constants of the complexes formed in aqueous solutions and their concentration distributions as a function of pH were evaluated at 25°C and ionic strength 0.10 mol·L−1 NaNO3. Respective stabilities of ternary complexes have been determined compared with the corresponding binary complexes in terms of Δlog  K and %R.S. values. A novel binary and ternary duloxetine (D) drug with glycine and its Cu(II) complexes has been synthesized and characterized by several spectroscopic methods. Electronic spectra and magnetic susceptibility measurements reveal square planar geometry for both complexes. The elemental analyses and mass spectral data have justified the [Cu(D)(Gly)] and [Cu(D)Cl(H2O)] composition of complexes, where D = duloxetine and Gly = glycine. The EPR spectra of Cu(II) complexes support the mononuclear structures. Thermal properties and decomposition kinetics of Cu(II) complexes are investigated.